Identification and optimization of hydrazone-gallate derivatives as specific inhibitors of DNA methyltransferase 3A. (March 2016) - Erdmann, Alexandre; Menon, Yoann; Gros, Christina; Masson, Véronique; Aussagues, Yannick; Ausseil, Fréderic; Novosad, Natacha; Schambel, Philippe; Baltas, Michel; Arimondo, Paola B
DNA methylation is the most studied epigenetic event. Since the methylation profile of the genome is widely modified in cancer cells, DNA methyltransferases are the target of new anticancer therapies. Nucleosidic inhibitors suffer from toxicity and chemical stability, while non-nucleosidic inhibitors lack potency. Here, we found a novel DNMT inhibitor scaffold by enzymatic screening and structure–activity relationship studies. The optimization studies led to an inhibitor containing three fragments: a gallate frame, a hydrazone linker and a benzothiazole moiety. Interestingly, the compound inhibits DNMT3A with micromolar potency (EC50 = 1.6 μM) and does not inhibit DNMT1; this DNMT3A selectivity is supported by a docking study. Finally, the compound reactivates a reporter gene in leukemia KG-1 cells.